2001
DOI: 10.1046/j.1524-4733.2001.40202-165.x
|View full text |Cite
|
Sign up to set email alerts
|

Pid7: Observational Evaluation of Health State Utilities Among a Cohort of Sepsis Patients

Abstract: OBJECTIVE: Among sepsis survivors, during recovery and thereafter, it is not established if patients resume or improve their quality of life. The study objective was to assess change in health status among sepsis survivors over a 6‐month period. METHODS: This was a prospective, multicenter, cohort study involving 701 patients with severe sepsis of presumed infectious origin from 53 hospitals. Patients' health status was assessed at day 30, 60, 90 and180 using EuroQoL‐5D and a visual analog scale. Instruments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…96,[109][110][111] The flow chart of the search results and inclusion/exclusion of the studies is provided in Figure 40. A summary of these studies is reported in Table 26.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…96,[109][110][111] The flow chart of the search results and inclusion/exclusion of the studies is provided in Figure 40. A summary of these studies is reported in Table 26.…”
Section: Resultsmentioning
confidence: 99%
“…In all four studies, 96,[109][110][111] utilities were derived using the EQ-5D instrument. The EQ-5D is a standardised instrument for use as a measure of health outcome and is applicable to a wide range of health conditions and treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, this estimate was recently used to assess the cost effectiveness of severe sepsis interventions [17]. This utility weight was obtained from a study of 6-month survivors of severe sepsis using the EuroQol-5D questionnaire [18,19].…”
Section: Life-years Gained and Quality-adjusted Life Yearsmentioning
confidence: 99%